Somatostatin analogue pasireotide (SOM230) inhibits catecholamine secretion in human pheochromocytoma cells. (1st January 2022) - Streit, Laura; Moog, Sophie; Hugel, Sylvain; Rame, Marion; Tanguy, Emeline; Andry, Virginie; Schmid, Herbert A.; Brunaud, Laurent; Bihain, Florence; Nominé-Criqui, Claire; Goumon, Yannick; Lacomme, Stéphanie; et al.
Abstract: Increasingly common, neuroendocrine tumors (NETs) are regarded nowadays as neoplasms potentially causing debilitating symptoms and life-threatening medical conditions. Pheochromocytoma is a NET that develops from chromaffin cells of the adrenal medulla, and is responsible for an excessive secretion of catecholamines. Consequently, patients have an increased risk for clinical symptoms such as hypertension, elevated stroke risk and various cardiovascular complications. Somatostatin analogues are among the main anti-secretory medical drugs used in current clinical practice in patients with NETs. However, their impact on pheochromocytoma-associated catecholamine hypersecretion remains incompletely explored. This study investigated the potential efficacy of octreotide and pasireotide (SOM230) on human tumor cells directly cultured from freshly resected pheochromocytomas using an implemented catecholamine secretion measurement by carbon fiber amperometry. SOM230 treatment efficiently inhibited nicotine-induced catecholamine secretion both in bovine chromaffin cells and in human tumor cells whereas octreotide had no effect. Moreover, SOM230 specifically decreased the number of exocytic events by impairing the stimulation-evoked calcium influx as well as the nicotinic receptor-activated inward current in human pheochromocytoma cells. Altogether, our findings indicate that SOM230 acts as an inhibitor of catecholamine secretion through a mechanism involving the nicotinic receptor and might be considered as a potential anti-secretory treatment for patients with pheochromocytoma. Highlights: The somatostatin analogue Pasireotide (SOM230) inhibits catecholamine secretion in tumor cells cultured from freshly resected human pheochromocytoma. SOM230 inhibits catecholamine secretion by reducing the number of exocytic events per tumor cell. SOM230 inhibits nicotine-induced calcium influx and impact the function of the nicotinic receptor in pheochromocytoma cells. Treatment of pheochromocytoma cells with octreotide has no effect on catecholamine secretion.